Correlation between Communication Competence and Brand Image with Purchasing Decisions of Product Sunlife Insurance - Widya Prasya, Dhira; Pradekso, M.Sc, Drs. Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Insurance companies in marketing their products can not be separated from the role of an insurance agent to sell its products. In addition, the role of brand image owned companies is also very important in consumer decision-making. This research is a quantitative study with explanatory type, which aims to determine the relationship of communication competence and brand image with product purchasing decisions. This research used theory of Speech Act and Reasoned Action theory. This study uses a non-probability sampling with technique type is purposive sampling with 60 peoples for sample, ages between 28-55 years old in the city of Yogyakarta were have been communicated with agent of insurance Sunlife. The results of Pearson correlation analysis shows that between competence communication of agent Sunlife insurance with product purchasing decisions have a significant relation, indicated by the significant value of 0.000 and its correlation coefficient of 0.727. Meanwhile the brand image with purchasing decisions of product also have a significant relation. This is demonstrated by the significant value of 0.000 and the value of the correlation coefficient is 0.802, it means there is a strong relations between brand image with purchasing decisions of product. From the analysis, it is known that the theory of Speech Act which says that communication competence of a person is important in the process of communication activities to achieve their goals in certain circumstances, including to influence other individuals as desired. In this study proved that an insurance agent who has good communication competence will be able to influence the prospective customers according to what they would expect that the decision to buy their product. Theory of Reasoned Action, said that consumer behavior, product purchases not because the behavior is not planned, not spontaneous, or implusive attitude of a consumer may be determined by his belief in the consequences of having a product of a particular company, also confirmed by the results of this study, which suggested a link strong between the brand image with purchasing decisions. Thus, the results of this study reinforce the Speech Act theory and Reasoned Action Theory.